Assessment of Factors Influencing Academic Performance of Nursing Students - Amoldeep1 , Bhawna Sharma2 , Sudhir Gupta3 , Jyoti Sarin4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Objectives: this study is intended to assess factors influencing academic performance of nursing students inselected institution.Methods: This is a descriptive cross sectional design conducted at Ambala, Haryana, India. 420 participants(308 females and 112 males) consisting of age group between 17 to 25 years were included. Responses werecollected by structured scale consisting of 22 items in 3 point scale.Results: Maximum students (88.6%) agreed that good and supportive relationship between teacher andstudents fosters better academic performance of students. A significant number felt that different teachingstrategies used by the nurse educators help to improve academic performance. More than half of thestudents (53.8%) disagree that students from low socioeconomic status have low scores in their academicperformance compared to their classmates with high socioeconomic status. From all of the academic factors,highest mean is of teacher related factors. There is a significant association found with mother’s education.Conclusion: These findings to be helpful for nursing college teachers and managers to advance academicperformance of students.